Postnatal epigenetic regulation of intestinal stem cells requires DNA methylation and is guided by the microbiome - Yu, Da-Hai (Genome Biol, 2015)
BACKGROUND: DNA methylation is an epigenetic mechanism central to development and maintenance of complex mammalian tissues, but our understanding of its role in intestinal development is limited. RESULTS: We use whole genome bisulfite sequencing, and find that differentiation of mouse colonic intestinal stem cells to intestinal epithelium is not associated with major changes in DNA methylation. However, we detect extensive dynamic epigenetic changes in intestinal stem cells and their progeny during the suckling period, suggesting postnatal epigenetic development in this stem cell population. We find that postnatal DNA methylation increases at 3′ CpG islands (CGIs) correlate with transcriptional activation of glycosylation genes responsible for intestinal maturation. To directly test whether 3′ CGI methylation regulates transcription, we conditionally disrupted two major DNA methyltransferases, Dnmt1 or Dnmt3a, in fetal and adult intestine. Deficiency of Dnmt1 causes severe intestinal abnormalities in neonates and disrupts crypt homeostasis in adults, whereas Dnmt3a loss was compatible with intestinal development. These studies reveal that 3′ CGI methylation is functionally involved in the regulation of transcriptional activation in vivo, and that Dnmt1 is a critical regulator of postnatal epigenetic changes in intestinal stem cells. Finally, we show that postnatal 3′ CGI methylation and associated gene activation in intestinal epithelial cells are significantly altered by germ-free conditions. CONCLUSIONS: Our results demonstrate that the suckling period is critical for epigenetic development of intestinal stem cells, with potential important implications for lifelong gut health, and that the gut microbiome guides and/or facilitates these postnatal epigenetic processes. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s13059-015-0763-5) contains supplementary material, which is available to authorized users.